Performance evaluation of conformal and straight cooling channels on injection moulded part - Abd. Rahim, Shayfull Zamree (2015)
In injection moulding process, warpage is one of the main quality aspects measured for moulded parts while cycle time to produce a part indicates the efficiency of the process. Efficient cooling is a huge challenge to many mould designers for achieving a uniform thermal distribution in an injection mould where it affects both quality and productivity. The use of conformal cooling design has been reported as very effective to distribute thermal uniformly, thus able to improve part quality as well as reducing moulding cycle time. However, most of previous researchers only focused on simulation studies and they hardly performed experimental works to verify the simulation results. In this study, a Milled Groove Square Shape (MGSS) conformal cooling channel has been designed, simulated, fabricated and tested using a front panel housing as the case study. Performance evaluations on the MGSS conformal cooling channel and straight cooling channel were conducted using simulation and experimental works in terms of quality (warpage) and productivity (cycle time) of the moulded part. Mould and coolant input temperatures were varied in both evaluations, i.e. mould temperature (40 oC to 80 oC) and coolant temperature (25 oC to 65 oC). Results showed that the MGSS conformal cooling was superior with improved cycle time from 37.57% to 48.66% (simulation) and confirmed by experimental trials (27.89% to 36.15%). Simulated results showed that there is no warpage on the front panel housing in x direction for both types of cooling channels. However, experimental results indicated that warpage occurs in x direction in both cooling channel designs, but MGSS conformal cooling type demonstrates more reduction from 36.36% to 76%. Similarly, warpage in y direction recorded a remarkable improvement within the range of 34.3% to 41.5% and 16.7% to 35.48% respectively from the simulated and experimental results when employing the MGSS conformal cooling channel. The fabrication cost of the MGSS conformal cooling channel is approximately 3 % to 5 % higher which depends on the complexity of part shape as compared to the straight cooling channel. The finding shows that the MGSS conformal cooling channel design offers very encouraging results which is able to improve part quality as well as productivity at an acceptable manufacturing cost.